Secretory Leukocyte Protease Inhibitor Is Present in Circulating and Tissue-Recruited Human Eosinophils and Regulates Their Migratory Function - Osiecka, Oktawia; Skrzeczynska-Moncznik, Joanna; Morytko, Agnieszka; Mazur, Angelika; Majewski, Pawel; Bilska, Bernadetta; Kapinska-Mrowiecka, Monika; Kosalka-Wegiel, Joanna; Pastuszczak, Maciej; Pyza, Elzbieta; Cichy, Joanna (Frontiers in Immunology, 2022)
Eosinophils and secretory leukocyte protease inhibitor (SLPI) are both associated with Th2 immune responses and allergic diseases, but whether the fact that they are both implicated in these conditions is pathophysiologically related remains unknown. Here we demonstrate that human eosinophils derived from normal individuals are one of the major sources of SLPI among circulating leukocytes. SLPI was found to be stored in the crystalline core of eosinophil granules and its dislocation/rearrangement in the crystalline core likely resulted in changes in immunostaining for SLPI in these cells. High levels of SLPI were also detected in blood eosinophils from patients with allergy-associated diseases marked by eosinophilia. These include individuals with eosinophilic granulomatosis with polyangiitis (EGPA) and atopic dermatitis (AD), who were also found to have elevated SLPI levels in their plasma. In addition to the circulating eosinophils, diseased skin of AD patients also contained SLPI positive eosinophils. Exogenous, recombinant SLPI increased numbers of migratory eosinophils and supported their chemotactic response to CCL11, one of the key chemokines that regulate eosinophil migratory cues. Together, these findings suggest a role for SLPI in controlling Th2 pathophysiologic processes via its impact on and/or from eosinophils.